Post-settlement dispersal: the neglected link in maintenance of soft-sediment biodiversity - Pilditch, Conrad A. (Biol Lett, 2015)
Seafloor integrity is threatened by disturbances owing to human activities. The capacity of the system to recover from disturbances, as well as maintain resilience and function, depends on dispersal. In soft-sediment systems, dispersal continues after larval settlement, but there are very few measurements of how far the post-settlers disperse in nature. Spatial scales of post-settlement dispersal are, however, likely to be similar to pelagic larval dispersal because of continued, frequent, small-scale dispersal over longer periods. The consequences of this dispersal may be more important for the maintenance of biodiversity and metacommunity dynamics than is pelagic larval dispersal, because of the greater size and competency of the dispersers. We argue that an increased empirical understanding of post-settlement dispersal processes is key for predicting how benthic communities will respond to local disturbances and shrinking regional species pools, with implications for monitoring, managing and conserving biodiversity.